An Investigation of Secondary School Students' Motivation and Addiction towards Digital Gaming by Age, Gender and Number of Siblings - Mehmet Oktay Kablan; Mehmet Imamoglu (Journal of Education in Science, Environment and Health)
The aim of this study was to examine the effects of gender, the number of siblings, and grade level on digital game playing motivation and addiction levels in secondary school students and to reveal the relationship between digital game motivation and addiction. A total of 394 students, 168 boys and 226 girls, participated in the study voluntarily. Personal Information Form, Digital Game Playing Motivation Scale, and Digital Play Addiction Scale for Children were used as data collection tools. Digital game playing situation (yes/no) was associated with gender and number of siblings (p< .05) but not with grade level (p> .05). The motivation and addiction levels for playing digital games are related to gender and grade level (p< .05) but not to the number of siblings (p> .05). There is a positive relationship between motivation and addiction to playing digital games (p< .05). In light of these findings, more effort should be made to prevent digital addiction in males according to gender and in 8th graders according to grade level.